Jewish art in context: the role and meaning of artifacts and visual images - Feuchtwanger-Sarig, Naomi; Irving, Mark; Schrijver, Emile G. L. (Studia Rosenthaliana, 2014)
Introduction -- The academic perspective -- 100 years of achievement in Jewish art Bezalel Narkiss -- Jewish art and visual culture: a century of academic achievement Vivian B. Mann -- Jewish material culture in historical contexts Falk Wiesemann -- The museum perspective -- Developing concepts at Amsterdam's Jewish Historical Museum Hetty Berg -- Relics of the Second World War: dealing with missing and misplaced objects in the Jewish Historical Museum collection Julie-Marthe Cohen -- Return of the future: the role of visual art in the contemporary Jewish museum Michaela Sidenberg -- The diasporic life of art and artifacts -- Sacrificial donations among the Romaniot Jews Ariella Amar -- Revitalizing the Jewish community of Erfurt: a treasure trove of visual culture Karin Szcech -- The Judeo-Persian carpets of Kashan: Zionist art and cultural craft manufactured in Iran Jihan-Jennifer Radjai -- On the Ketubbot of Verona as treasure chests of the community's past Stefania Roncolato